The basal transcription factor II H subunit Tfb5 is required for stress response and pathogenicity in the tangerine pathotype of Alternaria alternata. (10th August 2020) - Fu, Huilan; Chung, Kuang‐Ren; Gai, Yunpeng; Mao, Lijuan; Li, Hongye
Abstract: The basal transcription factor II H (TFIIH) is a multicomponent complex. In the present study, we characterized a TFIIH subunit Tfb5 by analysing loss‐ and gain‐of‐function mutants to gain a better understanding of the molecular mechanisms underlying stress resistance and pathogenicity in the citrus fungal pathogen Alternaria alternata . Tfb5 deficiency mutants (Δ Aatfb5 ) decreased sporulation and pigmentation, and were impaired in the maintenance of colony surface hydrophobicity and cell wall integrity. Δ Aatfb5 increased sensitivity to ultraviolet light, DNA‐damaging agents, and oxidants. The expression of Aatfb5 was up‐regulated in the wild type upon infection in citrus leaves, implicating the requirement of Aatfb5 in fungal pathogenesis. Biochemical and virulence assays revealed that Δ Aatfb5 was defective in toxin production and cellwall‐degrading enzymes, and failed to induce necrotic lesions on detached citrus leaves. Aatfb5 fused with green fluorescent protein (GFP) was localized in the cytoplasm and nucleus and physically interacted with another subunit, Tfb2, based on yeast two‐hybrid and co‐immunoprecipitation analyses. Transcriptome and Antibiotics & Secondary Metabolite Analysis Shell (antiSMASH) analyses revealed the positive and negative roles of Aatfb5 in the production of various secondary metabolites and in the regulation of many metabolic and biosynthetic processes in A. alternata. Aatfb5 may play a negative role in oxidative phosphorylation and a positive role in peroxisome biosynthesis. Two cutinase‐coding genes ( AaCut2 and AaCut15 ) required for full virulence were down‐regulated in Δ Aatfb5 . Overall, this study expands our understanding of how A. alternata uses the basal transcription factor to deal with stress and achieve successful infection in the plant host. Abstract : This study expands our understanding of how the tangerine pathotype of Alternaria alternata uses the TFIIH subunit Tfb5 to deal with stress and achieve successful infection in the plant host.